Exploring the impacts of social capital on preferences for air quality changes: A hybrid choice model approach - Hangjian Wu; Emmanouil Mentzakis; Marije Schaafsma (University of Athens, Department of Economics, International Economics and Development Laboratory (IEDL), 2025)
Air pollution is a globally recognised problem that causes premature deaths and economic loss. 95% of these premature deaths occur in developing countries, which often trade off investing in air quality improvement against economic growth. In these countries, economic growth may be prioritised by governments due to resource constraints, causing citizens to experience future air quality deterioration. Evidence from studies in developed countries suggests that social capital can be a potential impactful mediator urging the government to implement more pro-environmental policies. However, little empirical evidence exists for developing countries where environmental governance is often complicated by competing policy priorities. We investigated residents' preferences for clean air in Beijing, China, using a discrete choice experiment. In the experiment, attributes of air pollution were specified as either an improvement or a deterioration as a result of policy prioritisation. The effects of social capital (consisting of social trust, norms and networks) were examined by incorporating social capital indicators into a novel hybrid choice model. The results suggest that social capital was positively associated with individual preferences when air quality was projected to be improved (i.e., higher social capital leads to higher preferences for air quality improvement) as well as deteriorated (i.e., higher social capital leads to higher resistance to air quality deterioration). Our findings imply that in a society with high social capital, policymakers who prioritise economic growth at the expense of the environment are likely to cause considerable public welfare losses.
Keywords: D6; Q51; Q53; 330; Air quality; discrete choice experiment; social capital; social trust; social norms; social networks